Impact of Lecturer-Student Relationship on Student Academic Performance in Federal University, Oye-Ekiti - Leonard, Shaibu; Omotoyosi, Owalaye Faridat; Olumide, Anisulowo Bukola; Emmanuel, Sunday (Innovare Journal of Education, 2024)
The study investigated the impact of the lecturer-student relationship on student academic performance at Federal University, Oye-Ekiti, Ekiti state. A descriptive survey design was adopted. The study population comprised all Federal University, Oye-Ekiti undergraduates, totaling 25,000 students. A sample of 250 (10%) undergraduate students at Federal University, Oye-Ekiti, was randomly selected for the study. Three research questions and two hypotheses guided the study. The Lecturer-Student Relationship on Students’ Academic Performance Questionnaire was used as an instrument for data collection. Data collected was analyzed using percentage distribution, while the Pearson Product-Moment Correlation Coefficient was conducted to test the research hypotheses that guided the study at a .05 significance level. It was revealed from the analysis that (a) the level of lecturer-student relationship at Federal University, Oye-Ekiti, is high; (b) The analysis revealed that the nature of the lecturer-student relationship on student academic performance in Federal University, Oye Ekiti, was highly interpersonal relationships that bridged the gaps between lecturers and the students as well as lecturers and the community; and (c) The analysis also revealed that the impact of the lecturer-student relationship on the academic performance of males and females in Federal University, Oye Ekiti are improvement in personal growth, values, and attitudes, development of close personal relationships with other students, intellectual growth and interest in ideas, intellectual stimulation, and satisfied intellectual stimulation. It was recommended, among other things, that the university’s management should give incentives to lecturers who promote high relationships with students in schools.